Penggunaan KeLiP dalam pembelajaran bahasa Arab: Suatu tinjauan di Universiti Sultan Zainal Abidin - Khoirun Nisak, Mat Saad; Norasyikin, Osman; Kamarul Shukri, Mat Teh; Siti Salwa, Mohd Noor (2015)
E - learning has become a necessity in learning today because it has many advantages in the field of teaching and learning today. Its use in Arabic language learning is focused on because this subject is regarded as difficult to master by students learning it as a second language Thus, this study is aimed at examining the perception toward the use of e-learning (KeLiP) among students in an Arabic language course in Universiti Sultan Zainal Abidin (UniSZA). In particular, this article focuses on four main aspects: readiness, awareness, interest in the use of KeLiP and problems that exist throughout the learning process with KeLiP. The survey data were obtained from questionnaires distributed to 69 respondents in UniSZA. The results show that the majority of respondents are willing to use KeLiP, had the awareness of KeLiP, were interested in using it and said they do not face any problems when using KeLiP.